Avian Coloration Genetics: Recent Advances and Emerging Questions. (8th May 2021) - Price-Waldman, Rosalyn; Stoddard, Mary Caswell
Abstract: The colorful phenotypes of birds have long provided rich source material for evolutionary biologists. Avian plumage, beaks, skin, and eggs—which exhibit a stunning range of cryptic and conspicuous forms—inspired early work on adaptive coloration. More recently, avian color has fueled discoveries on the physiological, developmental, and—increasingly—genetic mechanisms responsible for phenotypic variation. The relative ease with which avian color traits can be quantified has made birds an attractive system for uncovering links between phenotype and genotype. Accordingly, the field of avian coloration genetics is burgeoning. In this review, we highlight recent advances and emerging questions associated with the genetic underpinnings of bird color. We start by describing breakthroughs related to 2 pigment classes: carotenoids that produce red, yellow, and orange in most birds and psittacofulvins that produce similar colors in parrots. We then discuss structural colors, which are produced by the interaction of light with nanoscale materials and greatly extend the plumage palette. Structural color genetics remain understudied—but this paradigm is changing. We next explore how colors that arise from interactions among pigmentary and structural mechanisms may be controlled by genes that are co-expressed or co-regulated. We also identify opportunities to investigate genes mediating within-feather micropatterning and the coloration of bare parts and eggs. We conclude by spotlighting 2 research areas—mechanistic links between color vision and color production, and speciation—that have been invigorated by genetic insights, a trend likely to continue as new genomic approaches are applied to non-model species. Graphical Abstract: